The Effect of Branching Strategies on Software Quality - Shihab, Emad; Bird, Christian; Zimmermann, Tom (Proceedings of the ACM/IEEE International Symposium on Empirical Software Engineering and Measurement, 2012)
Branching plays a major role in the development process of large software. Branches provide isolation so that multiple pieces of the software system can be modified in parallel without affecting each other during times of instability. However, branching has its own issues. The need to move code across branches introduces additional overhead and branch use can lead to integration failures due to conflicts or unseen dependencies. Although branches are used extensively in commercial and open source development projects, the effects that different branch strategies have on software quality are not yet well understood. In this paper, we present the first empirical study that evaluates and quantifies the relationship between software quality and various aspects of the branch structure used in a software project. We examine Windows Vista and Windows 7 and compare components that have different branch characteristics to quantify differences in quality. We also examine the effectiveness of two branching strategies – branching according to the software architecture versus branching according to organizational structure. We find that, indeed, branching does have an effect on software quality and that misalignment of branching structure and organiza-tional structure is associated with higher post-release failure rates.